HDPE/CNTs/CF shaped PEG-based phase change composite assisted by supercritical CO2. (10th April 2023) - Meng, Cong; Li, Xiaolong; Liu, Zhigang; Wang, Mingchao; Chen, Yi; Sheng, Yongji; Liu, Zhen; Xu, Yang; Jia, Ligeng; Wu, Lei; Chen, Xin; Li, Yi; et al.
Abstract: The inexhaustible solar energy is a non-negligible alternative to alleviate energy crisis, yet its intermittency and low light-thermal conversion efficiency have become the major challenges for material engineers. In this study, a green and facile supercritical CO2 foaming-assisted vacuum impregnation technique was applied to fabricate the shape-stability HDPE/CNTs/CF/PEG phase change composite (PCC). This advanced manufacturing technology concentrates the CNT and CF in HDPE porous foams, which increases the effective concentration of fillers, thereby enhancing the probability of fillers overlapping each other to form the electrically conductive and thermal conductive paths. Benefiting from this, the PCC is blessed with satisfactory thermal conductivity (0.653 W m −1  K −1 ), superior light-thermal conversion efficiency (98.1%), suitable phase change enthalpy (142.8 J g −1 ) and electromagnetic shielding property (19.01 dB). Accordingly, this favorable and facile preparation technology attach promising applications to PCCs in the fields of solar energy utilization, electromagnetic shielding, and thermal management. Graphical abstract: Image 1 Highlights: A facile scCO2 foaming-assisted vacuum impregnation was applied to fabricate PCC. ScCO2 foaming enriches filler, creating good thermal conductivity pathways. PCC displays light-thermal conversion efficiency (98.1%) and shape stability. PCC exhibits suitable EMI shielding effect and high energy storage density.